Idella : Marjorie Rawlings' "perfect maid" - Parker, Idella (University Press of Florida, 1992)
Idella Parker's recollections of Marjorie Kinnan Rawlings are as intimate and frank as their ten years together. This long-awaited memoir, written by the black woman who was cook, housekeeper, and comfort to the famous author from 1940 to 1950, tells two stories - one of their spirited friendship, the other of race relations in rural Florida in the days before integration. Personal details - Marjorie's abandon behind the wheel of her cream-colored Oldsmobile, her boiled.
Includes index.
Keywords: Rawlings, Marjorie Kinnan, -- 1896-1953 -- Friends and associates.; Parker, Idella.; Parker, Idella; Rawlings, Marjorie Kinnan, -- 1896-1953; Rawlings, Marjorie Kinnan.; Women household employees -- United States -- Biography.; Women authors, American -- 20th century -- Biography.; Florida -- Biography.; Employées de maison -- États-Unis -- Biographies.; Écrivaines américaines -- 20e siècle -- Biographies.; Floride -- Biographies.; BIOGRAPHY & AUTOBIOGRAPHY -- Literary.; LITERARY CRITICISM -- American -- General.; Friendship; Women authors, American; Women household employees; Florida; United States; Autobiografie; Biografie; American Literature.; English.; Languages & Literatures.; 1900-1999; Biographies